Attributes of Being as the Generative Basis and Object of Reflection in the Neuro-Linguistic System of the Substance of the Brain (Global Journal of Human-Social Science, 2025)
The article discusses the role of attributes of being as the basis for the formation and identification of universal internal integral universal properties of realities matter space-time continuum movement in the substance of the brain
Keywords: attribute of being; space-time continuum; syllogism; frame; deja vu; gemevu; preskevu; surrealism; cubism